Detection of Cytomegalovirus in Inflammatory Bowel Disease: A Retrospective Study. (21st September 2018) - Chen, Fengming; Liu, Yongjun; Ruggiero, Francesca
Abstract: Objectives: Cytomegalovirus (CMV) reactivation may exacerbate IBD and is associated with worse clinical outcome. Reported remission rate ranges from 67% to 100% after antiviral therapy. Histologic examination of the inflamed colon tissues, including H&E and immunohistochemistry (IHC), is considered the gold standard for diagnosing CMV colitis. Currently, there is no consensus on when to order CMV IHC, and the prevalence of CMV colitis in UC and Crohn disease patients was variable in different studies. In this study, we aimed to investigate (1) whether IHC may improve the CMV detection rate in IBD patients with moderate to severe inflammation and (2) the frequency of CMV positivity in patients with ulcerative colitis vs Crohn disease. Methods: We retrospectively reviewed our pathology database at Penn State Hershey Medical Center to identify colon biopsy and resection specimens performed in adult IBD patients with moderate to severe chronic active inflammation from July 1, 2016, to May 31, 2017. The H&E slides and IHC slides were re-reviewed. Fisher's exact test was performed to compare the frequency of CMV positivity between UC and Crohn disease patients. Results: The study included 202 colon specimens, comprising 68 specimens with UC, 132 with Crohn disease, and 1 with indeterminate IBD. Among them, 18 IHC tests were ordered in UC patients (18/68 = 26.5%) and 38 IHC tests were ordered in patients with Crohn disease (38/132 = 28.8%). IHC tests were positive in 3 UC patients (3/18 = 16.7%), but only 1 of them showed overt viral inclusion obvious on H&E. IHC tests were all negative in patients with Crohn disease (0/38 = 0%). Fisher test showed the frequency of IHC positivity is higher in UC patients ( P < .05). Conclusion: Our study demonstrated IHC can enhance CMV detection in inflamed colon tissues in IBD patients, especially in tissues with rare CMV-infected cells. Inconsistent with some other studies, we found patients with UC have a higher CMV infection rate than those with Crohn disease.